Proliferative glomerulonephritis with monoclonal immunoglobulin G deposits complicated by immunoglobulin A nephropathy in the renal allograft. (July 2016) - Sawada, Anri; Kawanishi, Kunio; Horita, Shigeru; Koike, Junki; Honda, Kazuho; Ochi, Ayami; Komoda, Mizuki; Tanaka, Yoichiro; Unagami, Kohei; Okumi, Masayoshi; Shimizu, Tomokazu; Ishida, Hideki; et al.
Abstract: Immunoglobulin (Ig) A nephropathy (IgAN) is a known autoimmune disease due to abnormal glycosylation of IgA1, and occasionally, IgG co‐deposition occurs. The prognosis of IgG co‐deposition with IgAN is adverse, as shown in the previous studies. However, in the clinical setting, monoclonality of IgG co‐deposition with IgAN has not been observed. We describe a case of proliferative glomerulonephritis with monoclonal IgG deposits (PGNMID) combined with IgAN in a renal allograft. A‐21‐year‐old man developed end‐stage renal failure with unknown aetiology and underwent living‐donor kidney transplantation from his mother 2 years after being diagnosed. One year after kidney transplantation, proteinuria 2+ and haematuria 2+ were detected; allograft biopsy revealed mesangial IgA and C3 deposits, indicating a diagnosis of IgAN. After tonsillectomy and steroid pulse therapy, proteinuria and haematuria resolved. However, 4 years after transplantation, pedal oedema, proteinuria (6.89 g/day) and allograft dysfunction (serum creatinine (sCr) 203.3 µmol/L) appeared. A second allograft biopsy showed mesangial expansion and focal segmental proliferative endocapillary lesions with IgA1λ and monoclonal IgG1κ depositions. Electron microscopic analysis revealed a massive amount of deposits, located in the mesangial and subendothelial lesions. A diagnosis of PGNMID complicated with IgAN was made, and rituximab and plasmapheresis were added to steroid pulse therapy. With this treatment, proteinuria was alleviated to 0.5 g/day, and the allograft dysfunction recovered to sCr 132.6 µmol/L. This case suggests a necessity for investigation of PGNMID and IgA nephropathy in renal allografts to detect monoclonal Ig deposition disease.